Peripheral vascular thrombo-embolism and the role of various fogarty arterial thrombo-embolectomy catheters: A comparative prospective study and its result. Issue 2 (2018) - Haridas, Arun Kumar; Bhat, Bharathi Shridhar
No abstract available